Association between perceived stress, multimorbidity and primary care health services: a Danish population-based cohort study. Issue 2 (24th February 2018) - Prior, Anders; Vestergaard, Mogens; Larsen, Karen Kjær; Fenger-Grøn, Morten
Abstract : Objectives: Mental stress is common in the general population. Mounting evidence suggests that mental stress is associated with multimorbidity, suboptimal care and increased mortality. Delivering healthcare in a biopsychosocial context is key for general practitioners (GPs), but it remains unclear how persons with high levels of perceived stress are managed in primary care. We aimed to describe the association between perceived stress and primary care services by focusing on mental health-related activities and markers of elective/acute care while accounting for mental–physical multimorbidity. Design: Population-based cohort study. Setting: Primary healthcare in Denmark. Participants: 118 410 participants from the Danish National Health Survey 2010 followed for 1 year. Information on perceived stress and lifestyle was obtained from a survey questionnaire. Information on multimorbidity was obtained from health registers. Outcome measures: General daytime consultations, out-of-hours services, mental health-related services and chronic care services in primary care obtained from health registers. Results: Perceived stress levels were associated with primary care activity in a dose–response relation when adjusted for underlying conditions, lifestyle and socioeconomic factors. In the highest stress quintile, 6.8% attended GP talk therapy (highest vs lowest quintile, adjusted incidence rate ratios (IRR): 4.96, 95% CI 4.20 to 5.86), 3.3% consulted a psychologist (IRR: 6.49, 95% CI 4.90 to 8.58), 21.5% redeemed an antidepressant prescription (IRR: 4.62, 95% CI 4.03 to 5.31), 23.8% attended annual chronic care consultations (IRR: 1.22, 95% CI 1.16 to 1.29) and 26.1% used out-of-hours services (IRR: 1.47, 95% CI 1.51 to 1.68). For those with multimorbidity, stress was associated with more out-of-hours services, but not with more chronic care services. Conclusion: Persons with high stress levels generally had higher use of primary healthcare, 4–6 times higher use of mental health-related services (most often in the form of psychotropic drug prescriptions), but less timely use of chronic care services.